Factors influencing the development of elite-level sports officials in Australia: the AFL, ABA and FFA*. Issue 9 (2nd September 2018) - Mack, Matthew; Schulenkorf, Nico; Adair, Daryl; Bennie, Andrew
Abstract: Previous research into sports officiating at the elite level has primarily focused on factors that impact negatively on sports officials, including experiences of abuse, time pressures and fear of failure. However, factors that have positively influenced the development of elite officials have largely been neglected. This is problematic, as a better knowledge about how elite officials progress to top-tier competitions may improve officiating performance and role satisfaction. This study therefore, aims to identify factors that work positively for individuals who seek to reach elite levels of sport officiating. This is important because it can assist our understanding of how to create a positive environment for the development of young officials, thereby helping with role satisfaction, improved chances of retention and, where appropriate, pathways into career development at the elite level of sport. The context for this study is Australia, with a focus on national competitions in basketball, football (soccer) and Australian Rules football as representative samples for referees and umpires.